Pola Terapi Diare Akut pada Balita Di Rumah Sakit Umum Daerah Ciawi - Sulawati, Ity; Cornelia, Celine; Feliks, Mikhael; N, Ivy Fu; Simatupang, Lestari; Angelina, Chesia; Christian, David; Rachmatullah, Fahmi (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Acute diarrhea is one of the most common diseases found in Indonesia. The prevalence of acute diarrhea in Indonesia in 2018 reached 37.88%, in most cases, viral in origin. The mortality rate for acute diarrhea was high among children aged <5 years. This study was conducted to examine the therapy pattern of acute diarrhea in toddlers. This study aims to find out whether the pattern of therapy for acute diarrhea in toddlers at the Ciawi Regional General Hospital is in accordance with WHO therapy standards and how the pattern of therapy for acute diarrhea in toddlers at the Ciawi Regional General Hospital. This research is a descriptive and was conducted in the SMF Department of Pediatrics, Ciawi Hospital. Data collection is carried out retrospectively using medical records starting from April 01, 2022 to June 30, 2022. Out of 78 samples, children afflicted with acute diarrhea is predominantly male (65.5%), aged 1-1.5 years (28%), with mild-moderate dehydration (57.7%) requiring hospitalization (61.5%). The most frequently administered pharmacological therapy was zinc (94.9%) followed by probiotics (92.3%), while ORS (15.4%) and antibiotics (12.8%) were given only in selective cases. This study found that the treatment pattern for acute diarrhea in children at RSUD Ciawi was generally in line with guidelines for the management of acute diarrhea according to WHO standards, where only 4 (5.1%) patients were outpatients who missed out zinc prescription. Keywords: Acute Diarrhea, Antibiotics, Probiotics, Toddler, Zinc  ABSTRAK Diare akut adalah salah satu penyakit yang banyak ditemukan di Indonesia. Prevalensi diare akut di Indonesia pada tahun 2018 mencapai 37,88%, sebagian besar disebabkan rotavirus. Angka mortalitas terbesar diare akut ditemukan pada anak usia <5 tahun. Karena itu, penelitian ini dilakukan untuk menelaah kesesuaian pola terapi diare akut pada balita. Penelitian ini bertujuan untuk mengetahui apakah pola terapi diare akut pada balita di Rumah Sakit Umum Daerah Ciawi sudah sesuai dengan standar terapi WHO dan bagaimana pola terapi diare akut pada balita di Rumah Sakit Umum Daerah Ciawi. Penelitian ini bersifat deskriptif dan dilakukan dibagian SMF Ilmu Kesehatan Anak RSUD Ciawi. Pengambilan data dilakukan secara retrospektif menggunakan rekam medis mulai dari 01 April 2022 hingga 30 Juni 2022. Dari 78 sampel, ditemukan penderita diare akut paling banyak berjenis kelamin laki-laki (65,5%), berusia 1-1.5 tahun (28%), dengan derajat dehidrasi ringan-sedang (57,7%) hingga memerlukan rawat inap (61,5%). Terapi farmakologik yang paling banyak diberikan adalah zink (94,9%) lalu diikuti probiotik (92,3%), sedangkan oralit (15,4%) dan antibiotik (12,8%) hanya diberikan pada kasus selektif. Penelitian ini menemukan pola terapi diare akut pada anak di RSUD Ciawi secara umum sesuai dengan pedoman tatalaksana diare akut menurut standar WHO, dimana hanya 4 (5,1%) pasien rawat jalan yang tidak mendapat zink. Kata Kunci: Antibiotik, Balita, Diare akut, Probiotik, Zink